The awesome Egyptians - Deary, Terry; Hepplewhite, Peter (New York : Scholastic, 1993)
A humorous look at ancient Egyptian history and civilization and those who helped to uncover it.
Keywords: Juvenile Literature; Egypt -- Civilization -- To 332 B.C. -- Juvenile literature